Isolasi dan Karakterisasi Bakteri Amilotermofilik Dari Sumber Air Panas Sungai Medang - Rahmadani Eka Pitri; Anthoni Agustien; Fuji Astuti Febria (Jurnal Biologi Universitas Andalas, 2015)
The research on isolation and characterization of amylothermophilic bacteria has been done in Research Laboratory of Microbiology, Biology Department, Mathematics and Natural Sciences Faculty, Andalas University, Padang. The aimed to obtain amylothermophilic isolate and describe their characteristic. The study used purposive sampling method and descriptive analysis. The study results obtained four amylothermophilic isolates with amylolitic index ranged from 2.23 until 3.51 were different macroscopic characters, rod shape, motile and produce catalase enzyme, three isolates  were  Gram positive and spore forming, one isolate was  Gram negative.